Length-weight relationship and condition factor of Liza parsia (Hamilton-Buchanan) in relation to industrial pollution - Rao, L M; Lakshmi, B Bharatha (Indian Journal of Fisheries, 2011)
The coastal waters of Visakhapatnam get polluted by the effluents of all Industries of Visakhapatnam. The effect of the industrial effluents on the length-weight relationship and condition factor of the mullet, Liza parsia, a frequent component of the local fishery was attempted. Gosthani estuary near Bhimili, a relatively unpolluted habitat situated at about 30 km away from the harbour area of Visakhapatnam, has been taken as the control station. The results of the study revealed that the length-weight relationship and condition factor were significantly less in the polluted harbour and coastal waters, compared to those from Gosthani waters. The details of the pollutants and the extent of their impact, specifically on the growth and fishery of L.parsia, have been dealt in this paper.